Rapidly Progressive Atrioventricular Block in a Patient with Sarcoidosis - Nagham Saeed Jafar; Warkaa Al Shamkhani; Sunil Roy Thottuvelil Narayanan; Anil Kumar Rajappan (Case Reports in Cardiology)
Cardiac sarcoidosis is a major cause of death in patients with systemic sarcoidosis. Cardiac manifestations are seen in 2.3% of the patients. Atrioventricular (AV) block is one of the common manifestations of cardiac sarcoidosis. Other presentations of cardiac involvement include congestive heart failure, ventricular arrhythmias, and sudden cardiac death. The presence of AV block in young patients should raise the suspicion of sarcoidosis. AV block may be the only manifestation and patients may not have clinical evidence of pulmonary involvement. Here we describe a young male presented with exercise induced AV block rapidly progressing to complete heart block with recurrent syncope needing urgent pacemaker implantation. Factors that suggested an infiltrative process included his young age, rapidly progressive conduction abnormalities in the ECG in the absence of coronary disease, and previous history of cutaneous sarcoidosis.